The evolving small-molecule fluorescent-conjugate toolbox for Class A GPCRs - Vernall, Andrea J.; Hill, Stephen J.; Kellam, Barrie (Wiley, 2014)
The past decade has witnessed fluorescently tagged drug molecules gaining significant attraction in their use as pharmacological tools with which to visualize and interrogate receptor targets at the single-cell level. Additionally, one can generate detailed pharmacological information, such as affinity measurements, down to almost single-molecule detection limits. The now accepted utilization of fluorescence-based readouts in high-throughput/high-content screening provides further evidence that fluorescent molecules offer a safer and more adaptable substitute to radioligands in molecular pharmacology and drug discovery. One such drug-target family that has received considerable attention are the GPCRs; this review therefore summarizes the most recent developments in the area of fluorescent ligand design for this important drug target. We assess recently reported fluorescent conjugates by adopting a receptor-family-based approach, highlighting some of the strengths and weaknesses of the individual molecules and their subsequent use. This review adds further strength to the arguments that fluorescent ligand design and synthesis requires careful planning and execution; providing examples illustrating that selection of the correct fluorescent dye, linker length/composition and geographic attachment point to the drug scaffold can all influence the ultimate selectivity and potency of the final conjugate when compared with its unlabelled precursor. When optimized appropriately, the resultant fluorescent conjugates have been successfully employed in an array of assay formats, including flow cytometry, fluorescence microscopy, FRET and scanning confocal microscopy. It is clear that fluorescently labelled GPCR ligands remain a developing and dynamic research arena.